1998
DOI: 10.1046/j.1365-2168.1998.00663.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative risk analysis and postoperative mortality of oesophagectomy for resectable oesophageal cancer

Abstract: The risk of death after oesophagectomy for oesophageal cancer can be assessed objectively before surgery and quantified by a composite risk score. This score provides a useful tool for refining the criteria of patient selection for resection or the choice of procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
1
19

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(205 citation statements)
references
References 18 publications
11
174
1
19
Order By: Relevance
“…In a minority of studies, older age was associated with an unfavourable postoperative outcome 44;49;52;53;55;56. The use of a risk score may be a quality indicator. Bartels et al evaluated a risk scoring model in a prospective setting and found a marked reduction in post-operative deaths due to better patient selection 57 .…”
Section: Patient Selectionmentioning
confidence: 99%
“…In a minority of studies, older age was associated with an unfavourable postoperative outcome 44;49;52;53;55;56. The use of a risk score may be a quality indicator. Bartels et al evaluated a risk scoring model in a prospective setting and found a marked reduction in post-operative deaths due to better patient selection 57 .…”
Section: Patient Selectionmentioning
confidence: 99%
“…A seleção cuidadosa de pacientes para a operação, visando a redução da morbidade pós-operatória, é atitude enfatizada e preconizada pela literatura médica 7,32,33,54,62 29,30,56 . Valorizam-se os níveis séricos de albumina 17 , sendo excepcional pelos autores a realização da operação em vigência de valores inferiores a 3g/dL.…”
Section: Discussionunclassified
“…Dentre os fatores responsáveis pela qualidade da anastomose, citam-se fatores intrínsecos ao procedimento, tais como anastomose realizada fora da cavidade abdominal, a ausência de camada serosa esofágica e a orientação longitudinal das fibras musculares da camada superficial do esôfago, que contribuem para a fragilidade da sutura nesta região. Dentre os fatores sistêmicos, podem-se citar desnutrição, hipotensão, hipoxemia, idade avançada, diabetes, icterícia, insuficiência respiratória ou renal e terapia neoadjuvante 5,6,54,60 .…”
Section: Tabela 1 -Dados Dos Dois Grupos Do Estudounclassified
See 1 more Smart Citation
“…Similarly, diseases like inflammatory bowel disease, mesenteric ischemia can also limit the use of colon and jejunum in such cases. 4,5 We present our experience of 32 such cases treated at tertiary care teaching institute in central India.…”
Section: Introductionmentioning
confidence: 99%